THE USE OF KATAKANA IN CITY NAMES IN JAVA ISLAND ON JAPANESE GOOGLE MAP - Asteria Permata Martawijaya; R Januar Radhiya (Jurnal Japanedu: Pendidikan dan Pengajaran Bahasa Jepang, 2019)
Japanese has different characteristics from other foreign languages including having kana letters, kanji and romaji. The kana letters include hiraganaand katakana. The katakanaletters are used to write loan word from foreign languages into Japanese. The names from outside Japan are also written using katakana. This study discusses about the writing of names of cities in Java island into Japanese katakanawhich contained in Japanese version of Google Maps. The aims of this study are to know how google.map.jp write the names of cities in Java island using Japanese katakanaand what pattern did they use to write those city’s names. The analysis conducted by using descriptive method. The results of this study revealed that in Japanese version of Google Map, there are 62 city names written in katakana, while the rest are written in romaji. There are eight patterns found in writing the name of the cities using katakana. Those are including writing katakanabased on Hepburnstyle using the KVKV pattern, adding vowels to each closed syllable sound, writing “r” for the sound of “l”, and syllable “ci” written as “chi (チ)” or “shi (シ)”.